Preparation of MWCNTs@SiO2 hybrids and its flame retardant synergistic effects with hyperbranched triazine‐based flame retardant on polypropylene. (9th July 2021) - Xu, Jiayou; Deng, Haiming; Luo, Minyi
Abstract: Intumescent flame retardant (IFR) which is composed of ammonium polyphosphate (APP) and hyperbranched triazine‐based char‐forming agent (HECA) is widely used in polypropylene (PP). However, how to reduce addition and improve the mechanical properties is still a problem. In this work, a new kind of MWCNTs@SiO2 hybrids which combine MWNTs and nano‐SiO2 was designed and prepared by the Stöber method. Results demonstrated that the MWCNTs@SiO2 hybrids can decrease the addition of IFR from 25 to 20 wt%, when 1 wt% of MWCNTs@SiO2 hybrids and 19 wt% of IFR were mixed and incorporated into PP, the flame retardant reached UL‐94 V‐0 rating, at the same time, reduce the heat release rate and smoke density of combustion. The reasons could be explained as MWCNTs@SiO2 improved the pyrolysis activation energy of PP/IFR and then improved the thermal stability of PP composites. MWCNTs@SiO2 hybrids formed a three‐dimensional network structure in PP/IFR composites and improved the shielding efficiency of PP/IFR char layer, which hindered heat and mass transfer, and then reduces heat release and smoke density. The formation of dense and continuous char layer during the combustion is considered as the contributing factor which is related to cooperation of MWCNTs@SiO2 and IFR. Abstract :